Genel Cerrahi Semiyoloji - Aykut, Abdurrahman; Ünal, Mücahit; Acar, Nebi; Akbulut, Muhammed Ali; Yavuz, Yunus Emre; Yaldız, Hasan; Kılınç, Ahmet; Metin, Şükrü Hakan; Bayraktar, Yahya Alperen; Yılmaz, Abdullah Hilmi; Balcı, Eray; Kayım, Sabahattin Oğuzhan (2023)
-